2022
DOI: 10.3390/jcm11237036
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the First and Second Wave of the SARS-CoV-2 Pandemic on Severe Trauma and the Care Structures in the German TraumaNetzwerk DGU®

Abstract: (1) Background: The aim of this study was to investigate the effects of the pandemic on transfer rates of severely injured patients within the German TraumaNetzwerk of the DGU. Furthermore, cause of accident, rescue times, and trauma cases are compared to pre-pandemic times. (2) Methods: For this investigation patients documented in the TraumaRegister DGU® from 2018 to 2020 were analyzed. The years 2018 and 2019 served as a comparison to 2020, the first COVID-19 pandemic year. All primary admissions and transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…During that phase, intensive care has been challenged a lot, and therapeutic changes may have occurred. However, separate analyses from the TR-DGU did not suggest that less trauma patients received intensive care, nor that length of stay did change during the pandemic ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…During that phase, intensive care has been challenged a lot, and therapeutic changes may have occurred. However, separate analyses from the TR-DGU did not suggest that less trauma patients received intensive care, nor that length of stay did change during the pandemic ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the European Commission report, with 66 road fatalities per million inhabitants, Poland remains one of the most dangerous countries to drive in Europe. In Germany, researchers reported a 3.7% decrease in car accidents and a 3.2% increase in bike accidents in a group of more than 40,000 severely injured patients from the German trauma registry during the lockdown [52]. According to the authors, social restrictions and an increase in those who switched to working from home resulted in less traffic and a decrease in MVCs.…”
Section: Injury Mechanismsmentioning
confidence: 99%
“…We observed a significant reduction in patient referrals with head trauma. Colcuc et al reported contradictory results in their multicenter analysis and recognized an increase in the percentage of head injuries during the lockdown period [52]. According to them, the lower physical activity in society with increased interest in bike-related sports were the reasons for this phenomenon.…”
Section: Anatomic Description Of Injurymentioning
confidence: 99%